PENCIPTAAN DESAIN RELIEF DAN PATUNG LOGAM WAYANG BEBER UNTUK IKON PARIWISATA PACITAN - Agus ahmadi; Sumadi sumadi; Fitri Murfianti (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT Wayang beber as a craftwork of original Pacitan art contains local wisdom, which requires conservation efforts, research, creation of wayang forms, performances and other alternative efforts, so that it can increase tourism in the Pacitan region. This research uses Wayang beber as a source of ideas in the creation of the Pacitan icon as a city of tourism. The results of this art design aim to produce design works, artwork in the form of reliefs and sculptures based on metal craft, and their future as exterior works. This method of creating works of art was carried out with a hermeunetic approach in the Pacitan and Surakarta regions. The research process and creation of craftworks are carried out through several stages, namely problem identification, planning, design image, and trials in the form of reliefs and sculptures based on metal craft art. The selection of the main character in wayang beber Pacitan is used as the basis for designing the work of new reliefs and sculptures, which are combined with the gunungan wayang motif and supplementary decorative motifs. The results of the selected pattern of this design are manifested into relief and sculpture works using metal materials including: brass plate, copper, aluminum with engraving techniques, special techniques for metal plate formation, desoldering and combined techniques of coloring using paint. Furthermore, the results of this metal-based craft work will be presented in the manufacturing process, the meaning of the motif, the form of the work and the location of its application in Pacitan.